pH infuence on oxygen mass transfer coeficient in a bubble column. Individual characterisation of kL and a - A. Ferreira (2013)
Experiments were performed in a laboratory scale bubble column (10 L), to investigate the pH influence on oxygen mass transfer coefficient, in order to achieve a better control of biological processes. The liquid-side mass transfer coefficient, kL, and the specific interfacial area, a, were studied individually. The specific interfacial area was obtained using the new automatic image analysis technique developed by Ferreira et al. (2012). The pH was changed by the addition to the system of the most common acids and base used in biological process: hydrochloric acid (HCl), phosphoric acid (H3PO4) and potassium hydroxide (KOH). The results show that aqueous systems containing HCl, H3PO4 or KOH present lower volumetric liquid side mass transfer coefficient, kLa, in relation to pure systems (distilled water), this decrease being not linear. It was found that the specific interfacial area presents higher values in KOH and HCl solutions in comparison with distilled water. However, an opposite behavior was observed in the liquid-side mass transfer coefficient values. The kL behavior on the impure systems was explained based on bubble surface contamination. Higbie's and Froessling's equations were adapted in the š present work in order to be used in bubble dispersion systems.